Preliminary Characterization of Two Small Insulinase-Like Proteases in Cryptosporidium parvum - Xu, Rui; Lai, Cong; Yang, Fuxian; Zhang, Qiang; Li, Na; Guo, Yaqiong; Xiao, Lihua; Feng, Yaoyu (Frontiers in Microbiology, 2021)
Cryptosporidium parvum is a major cause of moderate-to-severe diarrhea in humans and animals. Its compact genome contains 22 genes encoding divergent insulinase-like proteases (INS), which are poorly characterized. In this study, two small members of this family, INS-21 encoded by cgd7_2080 and INS-23 encoded by cgd5_3400, were cloned, expressed, and characterized to understand their functions. Recombinant INS-21 and INS-23 were expressed in Escherichia coli and polyclonal antibodies against these two proteins were prepared. The cgd7_2080 gene had a high transcription level during 0 h - 2 h of in vitro C. parvum culture, while cgd5_3400 was highly transcribed at 0 h - 6 h. INS-21 was mostly located in the apical region of sporozoites and merozoites whereas INS-23 were found as spots in sporozoites and merozoites. The immune-electron microscopy confirmed the expression of INS-21 in the apical region of sporozoites while INS-23 appeared to be expressed in the dense granules of sporozoites. The neutralization efficiency was approximately 35%, when the cultures were treated with anti-INS23 antibodies. These results suggest that INS-21 and INS-23 are expressed in different organelles and have might have different functions in the development of C. parvum.